A bioinformatics study on characteristics, metabolic pathways, and cellular functions of the identified S-nitrosylated proteins in postmortem pork muscle. (15th February 2019) - Liu, Rui; Zhang, Chaoyang; Xing, Lujuan; Zhang, Lili; Zhou, Guanghong; Zhang, Wangang
Highlights: We firstly studied the metabolic pathways of S-nitrosylation in postmortem pork. The motif of S-nitrosylated proteins was explored in postmortem pork muscle. The S-nitrosylated proteins mostly belong to enzyme involved in metabolic process. S-nitrosylation likely inhibits cell death of muscle cells in postmortem pork meat. Abstract: This study aimed to determine the characteristics, metabolic pathways and cellular functions of S-nitrosylated proteins from pork postmortem muscle using bioinformatics analysis. The results showed that S-nitrosylated proteins had a broad range of molecular weight and pI value and were mainly located in the functional region of secondary structure. The motif revealed the lysine (K) positioned at −5, −7, +1 and +5 through the S-nitrosocysteine while "C-X-X-C" was identified as the motif for non-S-nitrosylation-modified cysteine. The proteins were widely localized in cell compartments and mostly belonged to enzymes participating in the metabolic process. Glycolysis was the most significant pathways of S-nitrosylated proteins in postmortem muscle. The cell death of muscle cells was predicted to be inhibited by S-nitrosylation with the potential influence on the apoptosis. Those identified pathways and cellular functions of S-nitrosylation are proposed to have a profound influence on meat quality and should be highly regarded.